2013
DOI: 10.1016/s1836-9553(13)70199-1
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of challenge to the balance system is not reported in the prescription of balance exercises in randomised trials: a systematic review

Abstract: The review highlights a serious gap in the methods used to prescribe, implement, and evaluate the effect of balance exercise programs. Comprehensive work in this area is required to develop a psychometrically sound measure of balance exercise intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 46 publications
2
42
0
1
Order By: Relevance
“…However, one could argue that the intensity in terms of the difficulty to maintain balance during the exercises is more important and warrants the use of perturbations to train postural reactions (Farlie et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one could argue that the intensity in terms of the difficulty to maintain balance during the exercises is more important and warrants the use of perturbations to train postural reactions (Farlie et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is thus important to determine the difficulty of a balance task to be able to adapt and test the optimal training intensity to improve balance and postural responses during gait or other functional tasks. The level of challenge of any balance exercise is in general poorly evaluated or reported, likely due to the absence of adequate measure (Farlie et al, 2013). However, the level of challenge can be compared, as recently done between exergames and gait (Duclos et al, 2012) using the concepts of stabilizing and destabilizing forces to measure balance difficulty (Duclos et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Farlie and colleagues [15] completed a systematic review of measures of balance training intensity, examining 148 randomized trials. They found that intensity of balance was typically measured by some other aspect of the activity, such as exercise time, aerobic intensity, or a hierarchy of task difficulty without reference to the patient's ability.…”
Section: Editorialmentioning
confidence: 99%
“…We also have some guidelines related to the frequency and duration needed for an exercise program to be effective in certain setting and with certain populations [14]. However, we do not have a tool or measure to quantify the intensity aspect of balance tasks [15]. To be effective, a balance exercise program must be challenging; to induce any training effect, the exercise must be performed near an individual's capacity [9].…”
mentioning
confidence: 99%
“…There does not exist, however, a measure of balance exercise intensity. This has been pointed out in studies and reviews of balance exercise effectiveness: experts found balance exercise intensity terminology to be vague [7], and reviews have noted that there is no appropriate balance intensity measure at all, even though other dosage parameters are well defined [8,9]. Further, other dosage parameters or inappropriate, unrelated measures are often substituted for balance intensity [9,10].…”
Section: Introductionmentioning
confidence: 99%